Studies on biodegradability, morphology and mechanical properties of low density polyehtylene/sago based blends - Wan Abdul Rahman, Wan Aizan; Rasit Ali, Roshafima; Zakaria, Naterah (2006)
In this study, sago starch was physically blended with LDPE via two-roll mill to produces LDPE/sago starch (SS) bidegradable films. Glycerol was added to the blends as a plasticizer to increase the compatibility of sago starch and LDPE, which also subsequently reduced the brittleness of the film. Melt flow index of the blends was measured to determine the rheological properties and the viability of the blends to undergo blow film process. Gloss test was also studied to determine the optical properties. Mechanical and morphology studies of LDPE/SS biofilms have been done by tensile testing machine and microscopy respectively. Exposure of LDPE/SS biofilms to the fungi environment was done to analyse the biodegradability of the blends. Results showed, MFI of LDPE/SS biofilm decreased as the content of the starch increased as well as the glossiness of the films. The mechanical properties such as tensile strength and elongation also decreased as the starch content increased. However, biodegradablility of the films increased as the starch content increased as it can be seen by fungi growth on the surface of LDPE/SS biofilms.